Loss of normal anagen hair in pemphigus vulgaris. (1st July 2015) - Daneshpazhooh, M.; Mahmoudi, H. R.; Rezakhani, S.; Valikhani, M.; Naraghi, Z. S.; Mohammadi, Y.; Habibi, A.; Chams‐Davatchi, C.
Summary: Background: Pemphigus vulgaris (PV) is a known cause of loss of 'normal' anagen hair; that is, shedding of intact anagen hairs covered by root sheaths. However, studies on this subject are limited. Aim: To investigate anagen hair shedding in patients with PV, and ascertain its association with disease severity. Methods: In total, 96 consecutive patients with PV (new patients or patients in relapse) who were admitted to the dermatology wards of a tertiary hospital were enrolled in this study. Demographic data, PV phenotype, disease severity and presence of scalp lesions were recorded. A group of 10–20 hairs were pulled gently from different areas of the scalp (lesional and nonlesional skin) in all patients, and anagen hairs were counted. Disease severity was graded according to Harman score. Results: Anagen hair was obtained by pull test in 59 of the 96 patients (61.5%), of whom 2 had normal scalp. The mean ± SD anagen hair count was 5.9 ± 7.6 (range 0–31). In univariate analysis, anagen hair loss ( P < 0.01) and the presence of scalp lesions ( P = 0.01) were associated with severe disease. Mean anagen hair count was significantly higher in the severe (mean 6.83 ± 7.89) than the moderate (mean 1.06 ± 1.94) subgroup ( P < 0.001). Multivariate analysis confirmed anagen hair loss (OR = 1.16, 95% CI = 1.05–1.28, P < 0.01), but not scalp lesions ( P = 0.69) as an independent predictor of disease severity. Conclusions: According to our study, normal anagen effluvium is a frequent finding in patients with PV, and interestingly, this was observed in nonlesional as well as lesional scalp. In addition, severe anagen hair loss was an independent predictor of the disease severity.